2014
DOI: 10.1186/1880-5981-66-86
|View full text |Cite
|
Sign up to set email alerts
|

Non-volcanic seismic swarm and fluid transportation driven by subduction of the Philippine Sea slab beneath the Kii Peninsula, Japan

Abstract: To understand the mechanism of an intensive non-volcanic seismic swarm in the Kii Peninsula, Japan, we used a dense seismic linear array to measure fine-scale variations of seismic velocities and converted teleseismic waves. A low-velocity anomaly confined to just beneath the seismic swarm area is clearly imaged, which correlates spatially with an uplifted surface area and a highly conductive and strong attenuative body. These results suggest that fluids such as partial melt or water are present beneath this n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 41 publications
4
25
1
Order By: Relevance
“…Note that the vertical deviatoric strain and stress are not plotted in the figure, for the sake of simplicity. Here we presume that hot water or partial melt is acting as a heat source as proposed by Yoshida et al (2011) and Kato et al (2014) balanced with the surroundings), horizontal stress is expected to be 50 MPa smaller than the vertical stress at 0 km depth (horizontal tension) and 50 MPa larger at 10 km depth (horizontal compression). We must take the E-W compressional tectonic stress and effect of inhomogeneous structure also into account, but it is hard to evaluate them quantitatively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Note that the vertical deviatoric strain and stress are not plotted in the figure, for the sake of simplicity. Here we presume that hot water or partial melt is acting as a heat source as proposed by Yoshida et al (2011) and Kato et al (2014) balanced with the surroundings), horizontal stress is expected to be 50 MPa smaller than the vertical stress at 0 km depth (horizontal tension) and 50 MPa larger at 10 km depth (horizontal compression). We must take the E-W compressional tectonic stress and effect of inhomogeneous structure also into account, but it is hard to evaluate them quantitatively.…”
Section: Discussionmentioning
confidence: 95%
“…In the Wakayama region, heat flow data and seismic velocity structure indicate the presence of hot fluid beneath the hypocenters (e.g., Kato et al 2010Kato et al , 2014Matsumoto 2007;Omuralieva et al 2012;Tanaka et al 2004;Yoshida et al 2011). Nakajima and Hasegawa (2007) pointed out that high seismicity in this study area is probably related to locally concentrated fluids.…”
Section: Discussionmentioning
confidence: 99%
“…In the southwestern Japan, the detailed structure of the Philippine Sea plate has been revealed by extensive seismic studies (e.g., Hirose et al 2008a, b;Nakanishi et al 2008;Kato et al 2010Kato et al , 2014Nishizawa et al 2011). Comparing characteristics of seismic wave propagation between the southwestern Japan and Kanto area examined in this study could reveal more precise structure and fluid distribution in the subducting oceanic crust of the Philippine Sea plate.…”
Section: Dehydration Reactions In the Uppermost Oceanic Crust Of The mentioning
confidence: 88%
“…Seismic velocities and thickness of the uniform oceanic crust around source region well correspond to those estimated by tomography and seismic activities studies (Hori 2006;Kimura et al 2006;Hirose et al 2008a, b). In Tokai and southwestern Japan, using travel-time tomography, Hirose et al (2008b) and Kato et al (2010Kato et al ( , 2014 detected similar velocity changes in the oceanic crust of the Philippine Sea plate at depths beneath 40 km related with the overlying serpentinized fore-arc wedge mantle. Bostock et al (2002) analyzed scattered teleseismic waves and also reported velocity change at similar depths beneath the Cascadia.…”
Section: Dehydration Reactions In the Uppermost Oceanic Crust Of The mentioning
confidence: 99%
“…By comparing the analyzed chemical composition of hot water with modeled composition of dehydrated materials from downgoing oceanic crustal materials, the authors conclude that the water originates in the subducting oceanic plate (Matsumoto et al 2003;Kawamoto et al 2013;Kazahaya et al 2014). Within the same forearc region in the Kii peninsula, Japan, Kato et al (2014) report on an intensive non-volcanic seismic swarm and estimate a fine-scale seismic velocity structure of the region. The results indicate the presence of geofluids such as partial melt or water beneath the swarm.…”
Section: Introductionmentioning
confidence: 99%